Evaluation of the nutritional state of employee of feeding units of the São Francisco Valley - Cardozo, Jean da Silva (2019)
Food and Nutrition Unit (UAN) aims to provide balanced meals and promote healthy food to its clientele. There has been an increasing increase of overweight and obesity in the population in the last decades. The objective of this study was to evaluate the nutritional status of employees of the Food and Nutrition Unit of two university restaurants in Juazeiro-BA and the other in Petrolina-PE. A total of 24 people were evaluated, including weight, height, waist and hip circumference, and percentage of body fat, as well as data such as ethnicity, sex, age and occupation. Body mass index (BMI), hip ratio and waist / height ratio were used to evaluate the nutritional status of the individual. The highest prevalence was observed among overweight individuals with BMI greater than 24.9 kg / m², having high waist circumference and excess body fat. The present study found a higher prevalence of overweight, with risks of developing cardiovascular diseases in workers, indicating that the objectives of the PAT need to be taken into account, making nutritional assistance necessary in this group.